(پرسیاری رۆح لە شیعری نوێی كوردیدا بە نموونەی( گۆران، عباس ساڵح - حسێن, علی طاهر (Sulaimani Journal for Humanities, 2018)
The research focuses on the importance of soul from ancient times untill now, myth, religious discourse and modern philosophy. All of these have various answers for the question of soul and the literature also has focused on soul, especially poetry through aesthetics and poetic language. This research project consists of an introduction, two sections and references. The abstract of the research is also provided in English and Arabic. The first section deals with soul from the perspective of different discourses. The second section is a practical section which presents several examples from poems by Goran and Abbas Salih. These examples deal with soul through poetic language.